2017
DOI: 10.3233/jad-161067
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Physical Activity is Associated with Cerebral Glucose Metabolism in Adults at Risk for Alzheimer’s Disease

Abstract: The objective of this study was to investigate the relationship between accelerometer-measured physical activity (PA) and glucose metabolism in asymptomatic late-middle-aged adults. Ninety-three cognitively healthy late-middle-aged adults from the Wisconsin Registry for Alzheimer’s Prevention participated in this cross-sectional study. They underwent 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) imaging and wore an accelerometer (ActiGraph GT3X+) to measure free-living PA. Accelerometer data yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 48 publications
4
21
0
1
Order By: Relevance
“…Robinson et al's exercise intervention lasted only 12 weeks and consisted of approximately 35 total hours of training, which is substantially less than our 26-week intervention of approximately 58 hours of training. Furthermore, the type of training performed in their study included high intensity interval training, using 4 intervals of 4 minutes at 90% of VO 2 peak with 3 minutes of low intensity recovery between intervals; it is possible that moderate intensity PA is sufficient for promoting brain glucose metabolism [29]. More research is needed to understand how to better customize exercise dose (i.e., frequency, intensity, and duration) for targeted improvement in brain glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robinson et al's exercise intervention lasted only 12 weeks and consisted of approximately 35 total hours of training, which is substantially less than our 26-week intervention of approximately 58 hours of training. Furthermore, the type of training performed in their study included high intensity interval training, using 4 intervals of 4 minutes at 90% of VO 2 peak with 3 minutes of low intensity recovery between intervals; it is possible that moderate intensity PA is sufficient for promoting brain glucose metabolism [29]. More research is needed to understand how to better customize exercise dose (i.e., frequency, intensity, and duration) for targeted improvement in brain glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Standard accelerometer data inclusion criteria were used: at least 10 hours of valid wear time per day for a minimum of three weekdays and one weekend day [27]. Accelerometer data in 1-second epochs were processed using the sojourn-3 axis method [28] to calculate time spent sedentary and in light (LPA), moderate (MPA), and vigorous (VPA) intensity PA [28,29]. Briefly, this method utilizes data from vertical, anterior-posterior, and medial-lateral axes to identify independent bout intervals-time between starting one activity and transitioning to another-by instances of rapid acceleration or deceleration.…”
Section: Accelerometrymentioning
confidence: 99%
“…Vigorous intensity walking is a widely available form of exercise, achieved in many adults by brisk walking on an inclined treadmill or inclined terrain outdoors. Preliminary evidence suggests that moderate and vigorous, rather than light intensity exercise may be needed in order to realize benefit in brain glucose metabolism [68]. Finally, we wished to promote robust CRF adaption, which would be more likely by exceeding the minimum public health recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the secondary outcomes were selected to evaluate changes in key AD biomarkers including cerebral glucose metabolism, memory function, and hippocampal volume. Cerebral glucose hypometabolism was a valid outcome because it is a core feature of AD [74] and may be improved with aerobic exercise [10,68].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Schultz et al [23] found that CRF attenuated the adverse influence of cholesterol metabolism polygenetic risk on CSF biomarkers. Of note, the beneficial effect of PA on the brain substrates of cognitive health may depend on level of exercise intensity [70].…”
Section: Previous Findingsmentioning
confidence: 99%